Desa Sekura’s Tourism Prospects: Unlocking the Local Assets in Community Development - Iwan Ramadhan; Khosihan, Aan; Hardiansyah, Muhammad Agus; Daniel; Suriyanisa; Wiyono, Hadi (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2025)
Cultural heritage has been recognized as a relevant discourse in the planning of tourism village development within the international context; however, existing literature reveals certain limitations. A critical aspect of addressing this issue pertains to the integration of local assets into community empowerment initiatives. Consequently, this study seeks to investigate the tourism potential of Desa Sekura by employing an ethnography-based model of community empowerment that incorporates local assets. Utilizing an ethnographic methodology, this research examines the ways in which cultural traditions, social capital, and natural resources in Desa Sekura, West Kalimantan, Indonesia, can be leveraged to promote sustainable tourism development. The findings suggest that principles of social inclusion, community participation, and locally-based management can enhance the tourism potential of Desa Sekura while preserving its cultural identity. Furthermore, the evolution of local institutions in the management and utilization of cultural and social assets is effectively illustrated as a means of fostering tourism village potential. This study aims to contribute new perspectives on the development of tourism villages that emphasize local community empowerment and the preservation of cultural heritage as essential components of sustainable economic development.